Clinical practice guidelines for neonatal hypoxic-ischemic encephalopathy: A systematic review using the appraisal of guidelines for research and evaluation (AGREE) II instrument - Amer, Yasser S.; Anabrees, Jasim; Abdelmawla, Mohamed; Abdalgader, Ayman; Almazroei, Asmaa; Alhifzi, Ibrahim; AlOnazi, Abdullah Hawash; Sabr, Yasser; Hneiny, Layal; El-Malky, Ahmed; Alshalawi, Ayesha; Alayoubi, Ahmed; et al. (Frontiers in Pediatrics, 2023)
Abstract Background and Objective: To systematically review, critically appraise the quality of recent clinical practice guidelines (CPGs) for neonatal hypoxic ischemic encephalopathy (HIE), and map their recommendations. Data Sources: CPG databases (GIN, ECRI, NICE, SIGN, DynaMed), Bibliographic databases (PubMed, Embase, CINAHL), and related specialized professional societies (e.g. AAP, CPS, BAPM, RCPCH, and SNS). Study Selection: Original de-novo developed evidence-based CPGs for HIE, group authorship, Arabic or English languages, and international or national scope. The systematic review was drafted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement and Johnston et al methodological guide. Data Extraction Quality assessment of the included HIE CPGs by the Appraisal of Guidelines for REsearch & Evaluation II (AGREE II) Instrument and report their characteristics, AGREE II ratings, and recommendations Data Synthesis: Our search retrieved 2,489 citations, of which two recent HIE CPGs were eligible and appraised: Canadian Paediatric Society (CPS) and Queensland Maternity and Neonatal Services (QMN). The overall assessment of the QMN CPG was superior (83%). Domain 1 (Scope & Purpose) scored (47%, 63%), Domain 2 (Stakeholder Involvement) (72%, 39%), Domain 3 (Rigour of Development) (48%, 43%), Domain 4 (Clarity & Presentation) (100%, 96%), Domain 5 (Applicability) (59%,9%), and Domain 6 (Editorial Independence) (67%, 17%) for the QMN and CPS CPGs respectively. All appraisers recommended the QMN CPG for use in practice. Conclusion: The methodological quality of the QMN CPG was superior with the relevant recommendations for its use in neonatal practice. Limitations: limited to Arabic and English languages Registration: The protocol is registered in PROSPERO (CRD42021258291). Conflict of interest: None.